Peri-Hemorrhagic Edema and Secondary Hematoma Expansion after Intracerebral Hemorrhage: From Benchwork to Practical Aspects - Babi, Marc-Alain; James, Michael L. (Frontiers in Neurology, 2017)
Spontaneous intracerebral hemorrhage (SICH) is the most lethal type of stroke. Half of these deaths occur within the acute phase. Frequently observed deterioration during the acute phase is often due to rebleeding or peri-hematomal expansion. The exact pathogenesis that leads to rebleeding or peri-hemorrhagic edema remains under much controversy. Numerous trials have investigated potential predictor of peri-hemorrhagic edema formation or rebleeding but have yet to come with consistent results. Unfortunately, almost all of the “classical” approaches have failed to show a significant impact in regard of significant clinical outcome in randomized clinical trials. Current treatment strategies may remain “double-edged swords,” for inherent reasons to the pathophysiology of sICH. Therefore, the right balance and possibly the combination of current accepted strategies as well as the evaluation of future approaches seem urgent. This article reviews the role of disturbed autoregulation following SICH, surgical and non-surgical approaches in management of SICH, peri-hematoma edema, peri-hematoma expansion, and future therapeutic trends.